Comparative analysis of monoaminergic cerebrospinal fluid‐contacting cells in Osteichthyes (bony vertebrates). Issue 9 (29th March 2017) - Xavier, Anna L.; Fontaine, Romain; Bloch, Solal; Affaticati, Pierre; Jenett, Arnim; Demarque, Michaël; Vernier, Philippe; Yamamoto, Kei
Abstract: Cerebrospinal fluid‐contacting (CSF‐c) cells containing monoamines such as dopamine (DA) and serotonin (5‐HT) occur in the periventricular zones of the hypothalamic region of most vertebrates except for placental mammals. Here we compare the organization of the CSF‐c cells in chicken, Xenopus, and zebrafish, by analyzing the expression of synthetic enzymes of DA and 5‐HT, respectively, tyrosine hydroxylase (TH) and tryptophan hydroxylase (TPH), and draw an evolutionary scenario for this cell population. Due to the lack of TH immunoreactivity in this region, the hypothalamic CSF‐c cells have been thought to take up DA from the ventricle instead of synthesizing it. We demonstrate that a second TH gene ( TH2 ) is expressed in the CSF‐c cells of all the three species, suggesting that these cells do indeed synthetize DA. Furthermore, we found that many CSF‐c cells coexpress TH2 and TPH1 and contain both DA and 5‐HT, a dual neurotransmitter phenotype hitherto undescribed in the brain of any vertebrate. The similarities of CSF‐c cells in chicken, Xenopus, and zebrafish suggest that these characteristics are inherited from the common ancestor of the Osteichthyes . A significant difference between tetrapods and teleosts is that teleosts possess an additional CSF‐c cell population around the posterior recess (PR) that has emerged in specific groups of Actinopterygii . Our comparative analysis reveals that the hypothalamus in mammals and teleosts has evolved in a divergent manner: placental mammals have lost the monoaminergic CSF‐c cells, while teleosts have increased their relative number. Abstract : The authors demonstrate that hypothalamic CSF‐contacting neurons of chicken, Xenopus, and zebrafish express TH2 and TPH1 that encode dopamine and serotonin synthetic enzymes respectively. The comparative analysis suggests that this feature is conserved in bony vertebrates, while it has been secondarily lost in placental mammals.